2014
DOI: 10.1186/1746-1596-9-60
|View full text |Cite
|
Sign up to set email alerts
|

Operative versus conservative treatment for patellar dislocation: a meta-analysis of 7 randomized controlled trials

Abstract: PurposePatellofemoral pathology is common, and patellofemoral dislocation mainly affects adolescents and young adults. We conducted a meta-analysis exclusively of RCTs to compare the clinical outcomes of patellar dislocation patients managed operatively versus non-operatively.MethodsAfter systematic review of electronic databases and websites, a total of 7 RCTs reporting data on 402 subjects were included. The methodological quality of the literature was assessed using the PEDro critical appraisal tool. Mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…[11][12][13][14] These studies were published between 2011 and 2014, with all 4 performing a meta-analysis. One study reported a conflict of interest, 11 whereas 3 did not.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] These studies were published between 2011 and 2014, with all 4 performing a meta-analysis. One study reported a conflict of interest, 11 whereas 3 did not.…”
Section: Resultsmentioning
confidence: 99%
“…Reviews without meta-analysis [32][33][34][35] recommended conservative treatment except in several specific circumstances, such as presence of osteochondral fractures. On the contrary, recent meta-analysis [37][38][39][40][41][42], showed that surgical treatment significantly reduces the risk of redislocation. Moreover, surgical treatment was shown to improve Hughston VAS [36][37][38]40] and Tegner [38,39] scores.…”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, recent meta-analysis [37][38][39][40][41][42], showed that surgical treatment significantly reduces the risk of redislocation. Moreover, surgical treatment was shown to improve Hughston VAS [36][37][38]40] and Tegner [38,39] scores. Two papers [39,41] also reported higher Kujala score in short term (<5 years) follow-up, while evidence at six to nine years followup shifted towards conservative treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cheng et al (20) examined seven randomized prospective studies in their recent review, in which they evaluated functional results of conservative treatment and surgical treatment for first acute patellar dislocation and recurrence rates. They found that while recurrence rates were higher after conservative treatment, functional scores were better.…”
Section: Discussionmentioning
confidence: 99%